Pancreas cancer trials for early stage disease: Surgeons leading therapeutic cooperative group trials. Issue 1 (29th September 2021) - Snyder, Rebecca A.; Ahmad, Syed; Katz, Matthew H. G.
Abstract: Surgeon‐led clinical trials have defined the standard of care for locoregional pancreatic cancer to date. The infrastructure and collaborative nature of cooperative oncology groups offer many advantages, such as providing an ideal mechanism through which multidisciplinary pancreatic cancer trials are performed. As key members of the treatment team, surgeons bring experience and expertise to the design of surgical and multidisciplinary trials and are uniquely poised to be leaders of future pancreatic cancer trials.